Além dos 105 minutos: currículo cultural e (re)produção de modos de ser torcedor - Mauro Lúcio Maciel Júnior (2019)
Representing a cultural artefact of several countries around the world, soccer has become an object of investigations over the years and it is present in studies located in many fields of study. Motivating reflections ranging from sports performance to the implications of this sport in social life, this modality has been researched from different perspectives. With this in mind, considering the importance that soccer has in the existence of many of its admirers, the present study focuses on organizations of fans known in Brazil as torcidas organizadas. Bases on the curricular studies, especially in its post-critical perspective, I try to understand these institutions as formative spaces capable of deseminating content that influences the (re)production of specific ways of being a soccer fan. For this I worked directly with a group called Movimento 105 Minutos, located in the city of Belo Horizonte and known for representing Clube Atlético Mineiro in the bleachers, having inspirations in a specific supporting way characteristic of the barras present in diferente countries of Latin America. About Movimento 105, I am particularly interested in aspects that envolve the pedagogies put into action in the interactions of its participants, which are presented as constituent elements of a cultural curriculum capable of (re)producing fans. Seeking to know the elements that permeate construction of this artefact, I try to obtain answers to the following questions: How are the soccer fans that Movimento 105 wants to form? What are the contents in these formation processes? In what way are the knowledge transmitted? What meanings do they carry? In order to answer these questions, I focus on a work that combines bibliographical research, represented by the study of others authors works, and the field research, carried out through participant observations and semi-strutured interviews with the members of the Movimento 105. As results of almost eight months of immersion with the group on game days, the fieldwork brings elements that are organized into observation reports and archives with transcription of the interviews. For the discussion of these data, I approach concepts related to Michel Foucault´s discourse theory. Taking a post-struturalist perspective, I understand that language plays a constituent role in social dynamics and I seek to work the interactions in this group as social practices anchored in discourses that are important in the production of the behaviors of individuals. In this sense, when I come across the curriculum produced in this group, I see that there is the intention to train fans characterized by love, support and unconditional fidelity to Atlético. To that end, content that values these attributes is constantly reproduced by the fans, both in speeches and in actions. It is possible to say, therefore, that in order to approach these ideas, members of the Movimento 105 Minutos adopt a ritualized stance of supporting, using representations built on the barras to materialize this way of behaving like fans. In this contexto, the party in the bleachers becomes the main flag of the crowd. To this end, they support Galo as an essential condition to be part os the group and use material and simbolic elements (flags, bars, music, shirts, among others) to form na identity of the fans and convey ideals about a mode of be a supporter.